Evasion or permanence in the profession: educational policies and social representations of teachers - Ens, Romilda Teodora; Eyng, Ana Maria; Gisi, Maria Lourdes; Stiegler Ribas, Marciele (Revista Diálogo Educacional, 2014)
This paper considers the interference of changes in contemporary society in the teaching profession, especially in relation to the value attributed to teacher and his choice to continue in the profession. The research is based on the representations of teachers of elementary school regarding the choice of following or not the profession, and to do so, we take the context of teacher training in Brazil, in relation to the appreciation and professionalization of the teacher, to support the analysis of their representations. The results indicate that the representations about the profession related to permanence arise from problems such as: devaluation, low wages, difficulties concerning students’ behaviour and lack of working conditions for practicing the profession, because low investment in education. Such aspects may be reasons that justify why there are less people interested in teaching for basic education and many more abandoning education courses. Teachers who intend to continue in the profession reveal affective reason, without a critical analysis of policy issues and lack of objective conditions of work.